2021
DOI: 10.3126/jaim.v10i1.37085
|View full text |Cite
|
Sign up to set email alerts
|

Study of Endoscopic Findings in First Episode of Upper Gastrointestinal Bleeding

Abstract: Background and Aims: Upper gastrointestinal bleeding (UGIB) is one of the most common and grave emergencies encountered in Emergency department in Tertiary health care centre in our country. Upper endoscopy has a crucial role in the diagnosis and treatment of upper gastrointestinal bleeding. The aim of this study is to assess the endoscopic findings in patients presenting with first episode of UGIB. Methods: This was a hospital based cross sectional study of patients with haematemesis, melena or both who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Our studies showed almost half the proportion (47.06%) of upper GI bleeding is from variceal sources. Previous studies done in Nepal had shown a lesser prevalence that is 25 % in a study by Adhikari KR et al 8 and 23% in a study by Poudel MS et al 9 . The changing prevalence may reflect the different scenarios of the COVID lockdown period where the patients with minor GI bleeding may have been treated in the local primary health centre and only those with a large amount of bleeding or with co-morbidities referred to the tertiary health care centre like ours.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our studies showed almost half the proportion (47.06%) of upper GI bleeding is from variceal sources. Previous studies done in Nepal had shown a lesser prevalence that is 25 % in a study by Adhikari KR et al 8 and 23% in a study by Poudel MS et al 9 . The changing prevalence may reflect the different scenarios of the COVID lockdown period where the patients with minor GI bleeding may have been treated in the local primary health centre and only those with a large amount of bleeding or with co-morbidities referred to the tertiary health care centre like ours.…”
Section: Discussionmentioning
confidence: 79%
“…The mean age of the participants and the proportion of males were comparable with the other studies done previously in Nepal. [8][9][10] Among clinical parameters, the presence of jaundice, ascites, An accurate prediction of the cause of upper GI bleeding before the endoscopy procedure is important in a country like Nepal where there are few endotherapy centers besides a few major cities. This prior knowledge will enable clinicians to choose the most appropriate pharmacological therapy before performing the procedure or transferring to the higher facility center.…”
Section: Discussionmentioning
confidence: 99%